2016
DOI: 10.1111/raq.12148
|View full text |Cite
|
Sign up to set email alerts
|

Application of zeolites in aquaculture industry: a review

Abstract: Zeolites are microporous crystalline hydrated aluminosilicates, which have found various applications because of their very unique physicochemical characteristics such as ion exchange and adsorption–desorption properties. Significant progress has been made in recent years on applications of these inorganic adsorbents in different industries including agriculture, aquaculture, water and wastewater treatment, air purification and petrochemicals. This review article intends to summarize the published reports on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(82 citation statements)
references
References 105 publications
1
68
0
Order By: Relevance
“…Also, it has been approved by the FDA for usage in different agricultural related applications such as an anticaking agent in animal feeds (21 CFR 582-2727). Accordingly, natural zeolites are inert and nontoxic minerals which are classified as "Generally Recognized As Safe" in most applications as previously mentioned and exempted from regulations and reporting when used in accordance with good agricultural and veterinary practice (23). As feed additives, zeolites including CPL have been extensively used in farm animals to positively influence growth and reproductive performance, but most of all to improve gut health and general health status (14), and to improve welfare for other domestic animals, such as companion animals and horses (22).…”
Section: Health and Performance Promoting Zeolites In Veterinary Medimentioning
confidence: 99%
See 2 more Smart Citations
“…Also, it has been approved by the FDA for usage in different agricultural related applications such as an anticaking agent in animal feeds (21 CFR 582-2727). Accordingly, natural zeolites are inert and nontoxic minerals which are classified as "Generally Recognized As Safe" in most applications as previously mentioned and exempted from regulations and reporting when used in accordance with good agricultural and veterinary practice (23). As feed additives, zeolites including CPL have been extensively used in farm animals to positively influence growth and reproductive performance, but most of all to improve gut health and general health status (14), and to improve welfare for other domestic animals, such as companion animals and horses (22).…”
Section: Health and Performance Promoting Zeolites In Veterinary Medimentioning
confidence: 99%
“…Promising results have been obtained with natural, synthetic or modified clay minerals, zeolites (13) among which clinoptilolite (CPL) is the best known as zootechnical and biomedical feed ingredient widely reported in the scientific literature and used in farm animal nutrition as candidate to replace AGP in farm animals (14, 15) due to its unique antibacterial properties, safety and efficacy as dietary supplement, particularly reported for swine (16)(17)(18)(19). So far, CPL has been successfully used in animal biotechnology and veterinary medicine as the agent which is capable to ameliorate mycotoxicosis, maintain gut health by acting favorably on intestinal microbiota, reduce, prevent and treat diarrheal disease in farm animals, decrease the level of toxic heavy metals and ammonia, improve immunity, general health and growth performance in animals of veterinary and biomedical importance, and thus exhibiting potentials of both an IM and NC (4,[20][21][22][23][24]. In human medicine, the experiments in vitro and in vivo have suggested that CPL could be used as an adjuvant in immunodeficiency states and anticancer therapy, antioxidative agent or reducer of the levels of radionuclides (25-28).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some natural resin, such as zeolite, is used in removing ammonia from wastewater and clinoptilolite is one of the best zeolites in ammonia removal ion exchange process (Emadi et al, 2001;Farhangi & Rostami-Charati, 2012). Zeolites are microporous crystalline hydrated aluminosilicates, which have been used in various applications due to their unique physicochemical characteristics such as ion exchange and adsorption-desorption properties (Ghasemi et al, 2016). According to Yıldırım et al (2009), there are three main functions of natural zeolite benefits to aquacultures.…”
Section: Introductionmentioning
confidence: 99%
“…Even though there were many research conducted on the application of zeolite in fish culture, there is no specific dosage for specific fish culture. On top of that, it is considered to be an obstacle in application of zeolite for large-scale aquaculture (Ghasemi et al, 2016). The specific dose of zeolite is impossible to be recommended especially in fish rearing system.…”
Section: Introductionmentioning
confidence: 99%